Exploring the limits of exercise capacity in adults with type II diabetes - Matthijs Michielsen; Youri Bekhuis; Jomme Claes; Elise Decorte; Camille De Wilde; Tin Gojevic; Louise Costalunga; Sara Amyay; Varvara Lazarou; Daphni Daraki; Eleftheria Kounalaki; Panagiotis Chatzinikolaou; et al. (PLoS ONE, 2025)
Objective This study investigates the mechanisms behind exercise capacity in adults with type 2 diabetes mellitus (T2DM), focusing on central and peripheral components, as described by the Fick equation. Methods A cross-sectional study of 141 adults with T2DM was conducted, using cardiopulmonary exercise testing, near-infrared spectroscopy (NIRS) and exercise echocardiography. Participants with sufficient-quality NIRS data were stratified into tertiles based on percentage predicted VO₂peak. Group comparisons and stepwise regression were used to examine the contributions of central and peripheral components to VO₂peak. Results Sixty-seven participants had insufficient quality NIRS data. Those with lower-quality data were more likely to be female (p < 0.001) and had a lower exercise capacity (p < 0.001). Among participants with good-quality NIRS data, those in the lowest fitness tertile were older (p < 0.01), had a longer diabetes duration (p = 0.04), lower eGFR (p < 0.001) and more frequent use of beta-blockers (p = 0.02) and diuretics (p = 0.04). Significant differences were observed in peak cardiac output (p < 0.001) and NIRS-derived parameters across fitness groups. Multivariate regression identified cardiac output as the strongest predictor of VO₂peak, while peripheral oxygen extraction did not improve model performance. Conclusion Cardiac output is the primary determinant of exercise capacity in adults with T2DM. This suggests that muscle perfusion may be the main limiting factor in relatively fit individuals with T2DM. However, cardiac output and local muscle perfusion are not directly equivalent, as mechanical factors, such as intramuscular pressure during high-intensity exercise, may prevent maximal perfusion.